Cost of pediatric laryngotracheal reconstruction: Differences between single-versus double-stage procedures. (April 2023) - Drake, Marc; Lyon, Danielle; Martin, Timothy; McCormick, Michael; Jang, Minyoung; Griffith, Cynthia; Chun, Robert
Abstract: Objective: Examine differences in cost between single stage (ss) versus double stage (ds) laryngotracheal reconstruction (LTR) for pediatric subglottic stenosis. Study design: Retrospective chart review of children who underwent ssLTR or dsLTR from 2014 to 2018 at a single institution. Methods: Costs related to LTR and post-operative care up to one year after tracheostomy decannulation were extrapolated from charges billed to the patient. Charges were obtained from the hospital finance department and the local medical supplies company. Patient demographics including baseline severity of subglottic stenosis and co-morbidities were noted. Variables assessed include duration of hospital admission, number of ancillary procedures, duration of sedation wean, cost of tracheostomy maintenance, and time to tracheostomy decannulation. Results: Fifteen children underwent LTR for subglottic stenosis. D Ten patients underwent ssLTR, while five underwent dsLTR. Grade 3 subglottic stenosis was more prevalent in patients who underwent dsLTR (100%) than ssLTR (50%). The average per-patient hospital charges for ssLTR was 314, 383 versus 183, 638 for dsLTR. When estimated mean cost of tracheostomy supplies and nursing care until tracheostomy decannulation was included, the mean total charges associated with dsLTR patients was 269, 456. Average hospital stay after initial surgery was 22 days for ssLTR versus 6 days for dsLTR. Average time to tracheostomy decannulation for dsLTR was 297 days. Average number of ancillary procedures needed was 3 versus 8 for ssLTR versus dsLTR. Conclusion: For pediatric patients with subglottic stenosis, dsLTR may have a lower cost than ssLTR. Although ssLTR has the benefit of immediate decannulation, it is associated with higher patient charges, as well as longer initial hospitalization and sedation. For both patient groups, fees associated with nursing care comprised the majority of charges. Recognizing the factors that contribute to cost differences between ssLTR and dsLTR may be useful when performing cost-benefit analyses and assessing value in health care delivery.